Potential diagnostic consequences of applying non‐invasive prenatal testing: population‐based study from a country with existing first‐trimester screening. (25th February 2014) - Petersen, O. B.; Vogel, I.; Ekelund, C.; Hyett, J.; Tabor, A.; Christiansen, Marianne; Farlie, Richard; Hoseth, Eva; Ibsen, Mette Holm; Jensen, Hanne Søndergaard; Jørgensen, Finn Stener; Larsen, Torben; et al.
ABSTRACT Objectives Targeted non‐invasive prenatal testing (NIPT) tests for trisomies 21, 18 and 13 and sex chromosome aneuploidies and could be an alternative to traditional karyotyping. The aim of this study was to determine the risk of missing other abnormal karyotypes of probable phenotypic significance by NIPT. Methods This was a retrospective population‐based analysis of all singleton pregnancies booked for combined first‐trimester screening (cFTS) in Denmark over a 4‐year period. Data concerning maternal demographics, cFTS and prenatal or postnatal karyotypes were collected from the Danish Fetal Medicine database. Karyotypes were classified according to whether the chromosomal anomaly would have been detected by NIPT and whether it was likely to affect phenotype. Results cFTS was completed in 193 638 pregnancies. 10 205 (5.3%) had cytogenetic or molecular analysis performed. Of these, 1122 (11.0%) had an abnormal karyotype, of which 262 (23.4%) would have been missed by NIPT, but would probably have been clinically significant. The prevalence of such 'atypical abnormal karyotypes' was increased in women above 45 years of age, in pregnancies with increased nuchal translucency (NT) thickness (≥ 3.5 mm), with abnormal levels of free β‐human chorionic gonadotropin (< 0.2 or ≥ 5.0 multiples of the median (MoM)) or pregnancy‐associated plasma protein‐A < 0.2 MoM. One or more of these factors was present in 3% of women, and the prevalence of atypical abnormal karyotypes in this high‐risk cohort was 1.6%. Conclusions A significant proportion of karyotypic abnormalities will be missed by targeted NIPT. Women of advanced maternal age, or with increased fetal NT or abnormal biochemistry, have a higher risk of having a fetus affected by an atypical abnormal karyotype and need to be counseled accordingly when considering NIPT. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd